Corn (Zea mays) Emergence and Early Growth as Influenced by Tansymustard (Descurainia pinnata) Residue. Issue 1 (1st March 2014) - Werle, Rodrigo; Perez, Leonardo L.; Sandell, Lowell D.; Lindquist, John L.
Abstract : Farmers have observed reduced early growth of corn in the presence of tansymustard [ Descurainia pinnata (Walt.) Britt.], a winter annual weed of the Brassicaceae family. A greenhouse study was conducted to evaluate the effect of tansymustard on corn ( Zea mays L.) emergence and early growth. Treatments included corn growing in pots with only tansymustard root residue, with only tansymustard shoot residue, and with whole tansymustard plant residue (roots plus shoots); tansymustard plants treated with glyphosate 2 days after planting (DAP) corn seeds; and a control (no tansymustard residue). Corn emergence was recorded and biomass measured after 4 weeks of growth. Time to 50% corn emergence was delayed by 1 to 2 days when tansymustard plants were treated with glyphosate. The number of emerged corn plants per pot, total corn biomass per pot, and corn height were not influenced by the presence of tansymustard residue, leading to the conclusion that relatively low quantities of tansymustard residue had no effect on corn growth in this study. The stunted corn development observed by farmers in the field may be due to competition rather than allelopathy, since tansymustard is often controlled several days after crop emergence.